Evaluation of the Impact of PGRs in Bean Sprouts Extract on Vegetative Growth, Total Phenolics, and Antioxidant Activity of Chili Peppers, Soybeans, and Potatoes - Anggarani, Mirwa Adiprahara; Salsabilla, Auralia; Ansyaddad, Daud Zidane; Wuryaningrum, Ririt (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
This present study aims to evaluate the effect of administering natural growth regulators (PGRs) based on bean sprout extract (Vigna radiate) on vegetative growth, total phenolics, and antioxidant activity of chili pepper (Capsicum frutescens L.), soybean (Glycine max (L.) merrill), and potato (Solanum tuberosum L.) plants. Bean sprout extract was synthesized through maceration, employing 96% ethanol solvent with a ratio of solvent and simplicia at 1:5. The resulting extract was administered to the plant by means of watering starting at 7 days after planting (DAP) and continuing once every 7 days until the 13th week. Vegetative growth parameters, including plant height and number of leaves, were measured on a weekly basis. At the thirteenth week, the wet biomass, total phenolic content, and antioxidant activity were analyzed under various PGR treatments. All data were subjected to normality testing, followed by ANOVA or Kruskal–Wallis analysis. This was followed by DMRT or the relevant post-hoc tests. The results demonstrated that the application of bean sprout extract PGRs significantly enhanced plant growth, number of leaves, wet biomass, and total phenolic content in soybean plants. In addition, the application of bean sprout extract PGRs significantly enhanced the antioxidant activity of chili pepper and soybean plants. These findings highlight the advantages of bean sprout extract as a low-cost, renewable, and eco-friendly natural PGR, offering a sustainable alternative to synthetic growth regulators while enhancing plant growth and functional quality. The utilization of this natural PGR also supports eco-friendly agricultural practices and has the potential to increase horticultural crop productivity with minimal environmental impact.